PENGARUH LITERASI KEUANGAN, SIKAP KEUANGAN, LOCUS OF CONTROL DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN PADA PEGAWAI PERUMDA PALJAYA DI JAKARTA SELATAN - Dhias Dana Dhiksa; Astrid Dita Meirina Hakim (Nirta Learning Centre, 2026)
Financial behavior of employees at Perumda Paljaya often reflects complaints that their salaries are considered insufficient, even though nominally they are at a relatively adequate level. Financial behavior is an important aspect of individual economic decision-making and has become a major concern globally. This study aims to analyze and empirically examine the effects of Financial Literacy, Financial Attitude, Locus of Control, and Lifestyle on the Financial Behavior of Perumda Paljaya employees. This research uses a quantitative approach. The population determination technique employed was non-probability sampling. The population in this study consisted of 131 employees. The sampling method used was purposive sampling, resulting in a sample of 112 respondents, with data collected through direct-to-project questionnaire distribution. The data were analyzed using SPSS version 26 and Microsoft Excel 2019. The results show that Financial Literacy, Financial Attitude, and Locus of Control partially have a positive and significant effect on Financial Behavior, while Lifestyle has no effect on Financial Behavior.